Micro-computed tomographic evaluation of endodontic ledge position in relation to canal curvatures - Elio Berutti; Mario Alovisi; Edoardo Moccia; Massimo Carossa; Giovanni De Caro; Andrea Roccuzzo; Damiano Pasqualini; Nicola Scotti (BMC, 2022)
Abstract Background Endodontic ledge (EL) formation is the most common complication of endodontic treatment. Although various etiological factors have been identified, canal curvature is the most significant variable correlated with EL formation. The aim of this micro-computed tomographic (micro-CT) study was to evaluate EL position in the mesial canals of the lower molars in relation to the degree of canal curvature. Methods Forty intact mandibular first molars with independent mesial canals with 20°-40° primary mesio-distal curvature, 10°-30° buccal-lingual canal curvature and 4 < r ≤ 8 mm main curvature radius were selected. Working length was measured with a K-File #10 and a high resolution pre-operative micro-CT analysis was performed. Ledges were created at the point of maximum canal curvature using stainless steel K-Files #30-35, alternating irrigation with 5% NaOCl and 10% EDTA. A post-operative high-resolution micro-CT analysis was then completed. Pre- and post-operative images were analyzed. The angle (α) formed between the vector passing through the geometric center of the EL and the center of the original canal lumen and the line joining the centers of the mesio-buccal and mesio-lingual canal orifices was calculated, and a descriptive statistical analysis was achieved. The α angle values were analyzed in relation to canal curvature using Kruskal-Wallis and post hoc Dunn's tests. The level of significance was set at P < 0.05. Results The α angles appeared inversely proportional to canal curvatures in the buccal-lingual and mesio-distal projections. The mean α angle was 36.4° (standard deviation 10.64; 95% confidence interval 34.1-40.9). Conclusion Within the limitations of this study, endodontic ledges develop in the opposite direction to the three-dimensional canal curvature and their position is influenced by the degree of curvature. Clinically, the α angle values may be related to the recommended direction to manage endodontic ledges.